ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN BATUBARA - Fuadiantoni, Rahmad; -, Suratna; Mulyanto, Indro Herry (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2019)
Rahmad Fuadiantoni, Student Identity Number 152140102, Business Administration Study Program, Faculty of Social and Political Sciences, National Development University "Veteran" Yogyakarta. Title of research Analysis of Factors Affecting Capital Structure of Coal Companies Listed on Indonesia Stock Exchange Period 2012-2016. Advisor Suratna and IndroHerry Mulyanto.This study aims to determine the factors that affect the capital structure of coal companies listed on the Indonesia Stock Exchange either partially or simultaneously. This type of research is explanatory research. The sampling technique used is purposive sampling. Of the 22 coal companies listed on the Indonesia Stock Exchange, only 19 companies were taken as samples, because they have complete financial statements for 2012-2016. The analysis technique used is multiple linear regression analysis, which was previously tested with the classical assumption test and hypothesis testing using partial t test, simultaneous F test with a level of significance of 5%.The result of this research, asset structure has significant effect to capital structure. This is evidenced by a significance value of 0.017 (p ? 0.05). Operating leverage has a significant effect on capital structure. This is evidenced by a significance value of 0.036 (p ? 0.05). The level of sales growth has a significant effect on capital structure. This is evidenced by a significance value of 0.028 (p ? 0.05). Profitability has a significant effect on capital structure. This is evidenced by the significance value of 0.032 (p ? 0.05). Liquidity significantly affects the capital structure. This is evidenced by a significance value of 0.029 (p ? 0.05). Asset structure, operating leverage, sales growth rate, profitability, and liquidity simultaneously have a significant effect on the capital structure. This is evidenced by the significance value of F of 0.000 (p ? 0.05).          Conclusion, partially asset structure variables, operating leverage, sales growth rates, profitability, and liquidity have a significant effect on the capital structure. While simultaneously asset structure variables, operating leverage, sales growth rates, profitability (ROA), and liquidity have a significant effect on the capital structure. Research suggestions, for companies, companies should have plans and strategies in financial management to establish an optimal capital structure in order to maximize company profits and value. For financial management in determining the optimal capital structure should consider the factors that affect the capital structure of the asset structure, operating leverage, the level of sales growth, profitability, and liquidity. By considering these factors it is expected that the management will be easier in determining the optimal capital structure. For the researcher, for the next research should be able to use or add variables and samples in order to get better results and extend the period or time period in the observation, because the opportunity to obtain more information.